Looking at Organizational Change Through the Construction and Reconstruction of the Underpinning Values of the Organization Through Interactions Among Stakeholders - dos Santos Leitão, Sueli; Russi De Domenico, Silvia Marcia (Review of Business Management, 2015)
Objective – This paper attempts to understand how the stakeholders in an organization - which strives to achieve goals that are sometimes in conflict - construct and reconstruct (through their interactions) their beliefs (values related to organizational competition) and habits of action (practices). Design/methodology/approach – A qualitative single case study was conducted at a tax consulting firm in the service sector in Brazil, with ongoing organizational change. The firm seeks to find an even balance between fostering human and social development and financial earnings. Semi-structured and in-depth interviews were conducted with the founder, employees, customers and suppliers, in addition to nonparticipant observation, naturally occurring discussions, and documents. Findings – The analysis of the discursive materials showed that organizational practices reflect values formed over several years through the paradoxical tension between the world views of the founder on how the business world actually is and how it should be. The value of “coherence between what is said and what is done” permeated several reflexivity practices, when decisions were taken and the reasons underpinning them were discussed by management and employees, in pursuit of the goals initially proposed. Practical implications – This research contributes to wider-ranging reflections on the competitive world of organizations dealing with the challenges that face them, extending beyond social responsibility. It also illustrates that reflexivity may be particularly helpful in other forprofit organizations, particularly those focused on social innovation. Originality/value – This study promotes a discussion of change as a continuous process, grounded on a differentiated approach to organizational values, highlighting the emerging characteristics of organizational becoming.